THE EVALUATION OF THE CIVIL SERVANTS COMPETENCIES AT THE REGIONAL SECRETARIAT OF POHUWATO REGENCY - Azis Rachman; Syamsinah; Misdi Suji (Governance: Jurnal Ilmu Administrasi Publik, 2021)
The current study aims: 1) to evaluate the competence of civil servants in the Regional Secretariat of Pohuwato Regency; 2) to find out the efforts made by the Regional Secretariat of Pohuwato Regency in increasing the competence of civil servants. This research is a qualitative research with a descriptive-explanatory case study approach, which is to examine, analyze and describe. The results of the study: 1) the competence of civil servants in the Regional Secretariat of Pohuwato Regency is not sufficient, especially the knowledge of civil servants at the staff level. This can be seen from the aspect of knowledge of the dimensions of education, experience and interest in the main tasks and functions, which are still low, the skills in the dimensions of skills, personality and training are still very low with the percentage of skills only around 70%, mastery and use of technology in implementing their main tasks and functions during the Covid-19 pandemic. Attitude aspects, civil servants' discipline is still low, lack of responsibility for the main duties and functions, tolerance in carrying out tasks is still low and civil servants' lack of confidence in carrying out their duties; 2) efforts to improve the competence of civil servants at the Regional Secretariat of Pohuwato Regency by implementing Civil Service administration planning and developing the quality of civil servants, managing information systems on line with BKN, the Pavilion System. civil servants' performance accountability and supervision in the form of application of rewards and punishments through TPP and imposing sanctions according to the level of errors committed by civil servants